2017
DOI: 10.1111/jgs.14883
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dose Aspirin Use and Cognitive Function in Older Age: A Systematic Review and Meta‐analysis

Abstract: This review found no evidence that low-dose aspirin buffers against cognitive decline or dementia or improves cognitive test scores in RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 49 publications
1
27
0
2
Order By: Relevance
“…For instance, Kelley et al () do not find any significant relationship between the daily aspirin use and cognitive change over 2 to 6 years of follow‐up after controlling for the impact of age. Similarly, in another study (Veronese et al, ), aspirin does not influence the onset of dementia in observational studies and improve cognitive test scores in randomized controlled trials in older participants without dementia. One of the possible explanations for such contradictory findings could be linked to PPARα, a nuclear receptor that is abundant in the hippocampus (Roy, Jana, Corbett, et al, ; Roy, Jana, Kundu, et al, ; Roy and Pahan, ).…”
Section: Resultsmentioning
confidence: 78%
“…For instance, Kelley et al () do not find any significant relationship between the daily aspirin use and cognitive change over 2 to 6 years of follow‐up after controlling for the impact of age. Similarly, in another study (Veronese et al, ), aspirin does not influence the onset of dementia in observational studies and improve cognitive test scores in randomized controlled trials in older participants without dementia. One of the possible explanations for such contradictory findings could be linked to PPARα, a nuclear receptor that is abundant in the hippocampus (Roy, Jana, Corbett, et al, ; Roy, Jana, Kundu, et al, ; Roy and Pahan, ).…”
Section: Resultsmentioning
confidence: 78%
“…However, the effect of antiplatelet drugs on cognitive dysfunction remains controversial. While preclinical models have suggested that aspirin may decrease neuroinflammation and oxidative stress in the central nervous system [30], a recent meta-analysis suggested that there is no evidence that low-dose aspirin prevents cognitive dysfunction or improves cognitive test scores in randomized controlled trials [31]. In patients with PC, previous studies showed that medication use (antiplatelets, anticoagulants, and statins) had no correlation with dementia or AD in multivariate analysis [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, согласно действующим международным консенсусным рекомендациям использование антиагрегантов у пациентов с ФП, особенно в группе пожилых больных, следует ограничивать [42]. Недавний систематический обзор и метаанализ, который включал 8 наблюдательных и интервенционных исследований и 36 196 когнитивно интактных участников на исходном уровне, показал, что хроническое применение низких доз аспирина не было связано с глобальной когнитивной функцией или началом деменции [52].…”
Section: другие методы леченияunclassified